Hypoxic responsiveness and gut fermentation capacity in heart failure patients: preliminary results - Mikołajczak, Aleksandra; Seredyński, Rafał; Gonerska, Marzena; Sokolski, Mateusz; Paleczny, Bartłomiej; Ponikowska, Beata (Frontiers in Physiology, 2026)
BackgroundThe gut microbiota has emerged as a key contributor to cardiovascular regulation. Acute stimulation of microbial fermentation with lactulose enhances hypoxic ventilatory response (HVR) in healthy subjects, indicating increased peripheral chemoreceptor (PCh) responsiveness. Given that heart failure (HF) is characterized by PCh hyperactivity, this study investigated whether enhancing intestinal fermentation could acutely modify chemoreceptor-driven responses in HF patients.MethodsHF patients (n = 12; all males; age: 59.2[15.8]y; 67% in NYHA III) underwent transient hypoxia test twice: before and ∼120 min after ingesting a gut-fermentation-stimulating meal. Hydrogen in expired air was measured repeatedly and used to stratify the patients into high early fermentation (HEF) and low early fermentation (LEF) groups. Ventilatory (HVR) and cardiovascular (heart rate, blood pressure, systemic vascular resistance) responses to hypoxia were measured.ResultsHEF patients, as compared with the LEF group, displayed: (1) higher pre-lactulose HVR (mean ± SD, L/min/SpO2: 0.680 ± 0.284 vs. 0.343 ± 0.122; p = 0.024), (2) pre- and post-lactulose SVR response (mean ± SD, dyn s/cm5/SpO2: for pre-lactulose comparison, 35.40 ± 24.41 vs. 9.96 ± 1.80, p = 0.039; for post-lactulose comparison, 37.19 ± 25.75 vs. 9.22 ± 4.33, p = 0.026). HVR in the HEF group correlated with the net hydrogen excretion during the lactulose test (r = 0.85, p = 0.033).ConclusionOur preliminary results, derived from a small, uncontrolled physiological experiment conducted in 12 H F patients, imply a link between the upper gut microbial fermentation capacity and the baseline peripheral chemoreflex sensitivity in this population. Given the exploratory and non-randomized design, these findings should be interpreted with caution, and larger controlled studies are needed to confirm the nature and clinical relevance of this association.